Three-dimensional morphology of an ultrafine Al-Si eutectic produced via laser rapid solidification. (15th July 2023) - Zhou, Xinyi; Chao, Paul; Sloan, Luke; Lien, Huai-Hsun; Hunter, Allen H.; Misra, Amit; Shahani, Ashwin J.
Abstract: Al-Si alloys processed by laser rapid solidification yield eutectic microstructures with ultrafine and interconnected fibers. Such fibrous structures have long been thought to bear resemblance to those formed in impurity-doped alloys upon conventional casting. Here, we show that any similarity is purely superficial. By harnessing high-throughput characterization and computer vision techniques, we perform a three-dimensional analysis of the branching behavior of the ultrafine eutectic and compare it against an impurity-modified eutectic as well as a random fractal (as a benchmark). Differences in the branching statistics point to different microstructural origins of the impurity- and quench-modified eutectic. Our quantitative approach is not limited to the data presented here but can be used to extract abstract information from other volumetric datasets, without customization. Graphical abstract: